Искусство постмодерна: десакрализация мира и человека - Бобовникова, И.А. (Культура народов Причерноморья, 2014)
В статье рассматривается специфика постмодерна как парадигмы (А.Дугин) и ее
отражение в сфере искусства. В статті розглянуто специфіку постмодерну як парадигми (О.Дугін) та її відображення у
сфері мистецтва. In terms of the humanities postmodernism was abroad one hundred years ago. Today scientifically it
makes a great difference inter modern (as radical plurality of all the world and his wife) and modernism (as
programme of modern). In the article put to use idea of A.Dugin research history of humanity suth as allembracing
history of three paradigmes: Premodern, Modern and Postmodern. The author is not draw a parallel
between paradigms. He is give a slight idea: Premodern is tradition, religion and myth. Modern is all over no
Premodern. Postmodern in no all but impossible Premodern and Modern. It stands to reason Postmodern as
subject for investigation culturologe, also it’s at the top of one’s voice actually problem. In reality the art of
Postmodern found on and recapitulate it’s problem and reverberate in music, literature, cinematography,
architecture and other. Paradigm of Postmodern is discover good reason problems of the art and resort for
analysis desacrelization of the man and the world. It’s attach importance learned works of V. Veydle, H.Ortega y
Gasset, F. Jameson (“Postmodernism or the Cultural Logic of Late Capitalism”), Y. Deleuze (“Loguque du
sens”).